Pengaruh Persepsi Yang Baik Tentang Sistem Perpajakan, Motivasi Dan Sanksi Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dalam Membayar Pajak Pada KPP Pratama Medan Belawan - Mohd Idris Dalimunthe (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
Tax is a state income that is highly anticipated in recent years in financing state expenditure every year. The importance of taxes for development is not accompanied by compliance with paying taxes. The low compliance with paying taxes also occurred in the KPP Pratama Medan Belawan. Tax payment also occurred at the KPP Pratama Medan Belawan. This reserach aims to analyze the effect of good perception about the taxation system, motivation, sanctions on taxpayer compliance. Compliance research includes associative types. The sampling technique uses convenience sampling and accidental sampling with a total of 100 respondents. The test equipment used is the product when the correlation for validity and Cronbach's alpha for reliability testing. Assumptions used are normality, multicollinearity and heteroscedasticity. Data analysis uses multiple linear regression. The results show that a good perception of the taxation system affects taxpayer compliance, motivation influences taxpayer compliance, and sanctions also affect taxpayer compliance. Simultaneously a good perception of the taxation system, motivation and sanctions affect taxpayer compliance. The better the tax system that is built will increase taxpayer compliance. The motivation of taxpayers continues to be built by conducting socialization and workshops by inviting taxpayers to the Pratama Medan tax service office. The application of sanctions will give a tax effect to taxpayers in increasing individual taxpayer compliance